A Cross-Sectional Evidence-Based Review of Drug Promotional Literature (DPL) in a Government Medical College (Indian Journal of Public Health Research & Development, 2024)
With the increase in the number of new drugs and high competition among pharmaceutical companies, medical representatives use DPL to promote their drugs. DPLs are one of the most accessible means of drug information. Therefore, drug promotion by ethical means is important as it influences rational and ethical prescribing by clinicians. This study was undertaken to evaluate and analyze the various DPLs for their ethical and scientific status as per WHO Ethical Drug Promotion Guidelines. This is a cross-sectional, observational study, conducted by evaluating and analyzing 207 DPLs collected randomly over a period of 6 months from various OPDs of Jorhat Medical College and Hospital. Of the 207 DPLs, a single drug was promoted in 48.31% and 51.69% were drug combinations. Only 60 (28.98%) of the DPLs fulfilled all 11 WHO criteria. References were mentioned in 75.85%; adverse drug reactions, contraindications, precautions, warnings, and drug interactions were listed in 32.85% of brochures, while dosage regimen was mentioned in 64.73% DPLs. The drug cost was highlighted in 7 DPLs (3.38%), while 2 DPLs (0.97%) did not mention the manufacturer’s name. Although 21.74 % literature showed relevant graphs and tables, 3% of brochures had irrelevant pictures. The most commonly promoted drugs were those acting on CNS (15.94%), followed by drugs acting on the cardiovascular system and anti-diabetic drugs (13.04%). In conclusion, majority of the DPLs did not follow the WHO guidelines and hence inadequate and unreliable drug information was promoted; which may mislead and result in irrational or unethical prescriptions.
Keywords: DPL, Drug Promotional Literature,Medical Representatives.